TYPOLOGICAL OVERVIEW OF TOURISM AND THE ADVENT OF NEW TYPES OF TOURS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reviews ‘types of tourism’. The origins and evolution of types of tourism are pinpointed through both chronological and thematic literature reviews. A conceptual model of the traditional and new types of tourism is provided, identifying research gaps, and assisting professional practice.